Studi Eksperimental Penukar Kalor Pipa Ganda Helical Pada Sistem Refrigerasi Joule-Thomson - Sunardi, Cecep; Suhanan, Suhanan; Prajitno, Prajitno (Jurusan Teknik Refrigerasi dan Tata Udara, Politeknik Negeri Bandung, 2012)
The Joule-Thomson refrigeration system currently is being developed for cryogenic application to substitute Linde-Hampson refrigeration system. The advanted of the Joule-Thomson refrigeration system is lower operating pressure than the Linde-Hampson refrigeration system. The Joule-Thomson refrigeration system works in pressure about 20 bar, while the Linde-Hampson refrigeration system in about 200 bar. To get the desire cryogenic temperature, in the Joule-Thomson refrigeration system, ussually is used mixed refrigerants, whereas in this investigation is only used one refrigerant, that is R-22. The one of the Joule-Thomson refrigeration system performance parameters is heat exchanger effectiveness ( ). To know the effect of diameter size to the effectiveness, heat transfer coefficient and Joule- Thomson cycle performance, in this research a helical double pipe heat exchanger is used in three variations of coil size diameter, those are : 18,5 cm, 22 cm and 27 cm of coil diameter size. The evaporator is investigated in two variation, such as : insulated tube and bare tube. The results are : the highest of effectiveness ( ) of heat exchanger is 88 % at the smallest coils diameter (18,5 cm), the highest overall heat transfer coefficient (U) is 431 W/m2.K at the smallest coils diameter (18,5 cm). The highest COP actual and refrigeration efficiency are 3,15 and 73,3 % both are at the widest coils diameter (27 cm).